Analysis models for unguided search in unstructured P2P networks. (16th July 2008) - Wu, Bin; Kshemkalyani, Ajay D.
Random walk and flooding are basic mechanisms for searching unstructured overlays. This paper shows that node coverage is an important metric for query performance in random graph based P2P networks. We then present two analytical models: the algebraic model and the combinatorial model. These models are useful in setting query parameters and evaluating search efficiency. We evaluate these two models in terms of various performance metrics against simulation results. We also study the impact of the setup parameters, such as node degree, hop count, and number of walkers, on the query performance, and on the precision of the models.